DEVELOPING PRESCHOOL TEACHER COMPETENCIES AND WELL-BEING FOR THE DIGITAL AGE: A CONCEPTUAL FRAMEWORK - Yang, Xinyue; Abdul Rahman, Mohd Nazri (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This concept paper aims to explore the dual challenge faced by preschool educators in the digital age—developing digital competencies while maintaining psychological well-being. Method: Using a conceptual qualitative approach, this study conducted a thematic synthesis of recent literature from 2018 to 2024 across multiple international databases. The analysis was guided by established educational and psychological frameworks including DigCompEdu, PERMA, and the Job Demands-Resources (JD-R) model.  Results: The study identifies three key domains crucial for preschool teacher development: digital pedagogy competencies, socio-emotional well-being, and professional sustainability. These domains are synthesized into a proposed framework that offers integrated solutions. Novelty: The proposed framework bridges a gap in existing research by integrating digital skill development and teacher well-being, specifically within the underexplored context of early childhood education.